Komparasi Kompetensi Kepemimpinan Klinis Perawat Primer Berdasarkan Perspektif Evaluasi Diri dan Evaluasi Kepala Ruangan - Liana Ginting; F. Sri Susilaningsih; Yayat Suryati; Blacius Dedi (Jurnal Keperawatan Silampari, 2022)
This study aims to examine the clinical leadership competence of primary nurses based on the perspective of self-evaluation and evaluation of the head of the room in the inpatient room at Immanuel Hospital, Bandung. This research method is a quantitative research using a comparative research design. The results showed that there was 1 component had an evaluation equation, namely the element of working together with other people both in the primary nurse self-evaluation and the evaluation of the head of the ward had good cooperation. Four components had different evaluation results between the primary nurse's self-evaluation and the evaluation of the head of the room, namely, self-quality, management of nursing care services, improving services, and determining direction. In conclusion, there are differences in the clinical leadership competence of primary nurses based on the primary nurse's self-evaluation with the evaluation of the head of the room. Keywords: Self Evaluation, Head of Room Evaluation, Clinical Leadership, Primary Nurse